Heterogeneous Coprecipitation of Nanocrystals with Metals on Substrates - Yandi* Hu; Zhang, Suona; Zhou, Zehao; Zhiqian Cao (Accounts of Chemical Research (Cover Article), 2024)
The heterogeneous coprecipitation of nanocrystals with metals on substrates plays a significant role in both natural and engineered systems. Due to the small dimensions and thereby the large specific surface area, nanocrystal coprecipitation with metals, which is ubiquitous in natural settings, exerts drastic effects on the biogeochemical cycling of metals on the earth’s crust. Meanwhile, the controlled synthesis of nanocrystals with metal doping to achieve tunable size/composition enables their broad applications as adsorbents and catalysts in many engineered settings. Despite their importance, complex interactions among aqueous ions/polymers, nanocrystals, substrates, and metals are far from being well-understood, leaving the controlling mechanisms for nanocrystal formation with metals on substrates uncovered. In this Account, we discuss our systematic investigation over the past 10 years of the heterogeneous formation of representative nanocrystals with metals on typical substrates. We chose Fe(OH)3 and BaSO4 as representative nanocrystals. Mechanisms for varied metal coprecipitation were also investigated for both types of nanocrystals (i.e., Fe, Al, Cr, Cu, and Pb)(OH)3 and (Ba, Sr)(SO4, SeO4, and SeO3)). Bare SiO2 and Al2O3, as well as those coated with varied organics, were selected as geologically or synthetically representative substrates. Through the integration of state-of-the-art nanoscale interfacial characterization techniques with theoretical calculations, the complex interactions during nanocrystal formation at interfaces were probed and the controlling mechanisms were identified. For BaSO4 and Fe(OH)3 formation on substrates, the local supersaturation levels near substrates were controlled by Ba2+ adsorption and the electrostatic attraction of Fe(OH)3 monomer/polymer to substrates, respectively. Meanwhile, substrate hydrophobicity controlled the interfacial energy for the nucleation of both nanocrystals on (in)organic substrates. Metal ions’ (i.e., Cr/Al/Cu/Pb) hydrolysis constants and substrates’ dielectric constants controlled metal ion adsorption onto substrates, which altered the surface charges of substrates, thus controlling heterogeneous Fe(OH)3 nanocrystal formation on substrates by electrostatic interactions. The sizes and compositions of heterogeneous (Fe, Cr)(OH)3 and (Ba, Sr)(SO4, SeO4, SeO3) formed on substrates were found to be distinct from those of homogeneous precipitates formed in solution. The substrate (de)protonation could alter the local solution’s pH and the substrates’ surface charge; substrates could also adsorb cations, affecting local Fe/Cr/Ba/Sr ion concentrations at solid–water interfaces, thus controlling the amount/size/composition of nanocrystals by tuning their nucleation/growth/deposition on substrates. From slightly supersaturated solution, homogeneous coprecipitates of microsized (Ba, Sr)(SO4, SeO4, SeO3) formed through growth, with little Sr/Se(VI) incorporation due to higher solubilities of SrSO4 and BaSeO4 over BaSO4. While cation enrichment near substrates made the local solution highly supersaturated, nanosized coprecipitates formed on substrates through nucleation, with more Sr/Se(VI) incorporation due to lower interfacial energies of SrSO4 and BaSeO4 over BaSO4. The new insights gained advanced our understanding of the biogeochemical cycling of varied elements at solid–water interfaces and of the controlled synthesis of functional nanocrystals.